2003
DOI: 10.1046/j.1440-172x.2003.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between psychosocial factors and happiness among school adolescents

Abstract: The concept of health contains aspects of social and mental well-being and not just the absence of disease. The concept of well-being is sometimes used interchangeably with the term happiness, although focus has been on other aspects as well. Here we explore associations between happiness and experience of stress at school, personal and social factors among 887 Norwegian school adolescents participating in a World Health Organization project on health-promoting schools. Happiness was measured by a one item que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
147
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(172 citation statements)
references
References 51 publications
14
147
1
10
Order By: Relevance
“…Generally, in Pakistan girls face more social rejection than boys which may be ascribed to their low SWB. While, Natvig et al (2003) found no significant differences between boys and girls with respect to their reported level of subjective well-being. However, the Present finding is in contradiction with the finding of Haller and Hadler (2006) who found that women scored significantly higher both on happiness and life satisfaction in every field of life.…”
Section: Discussionmentioning
confidence: 57%
“…Generally, in Pakistan girls face more social rejection than boys which may be ascribed to their low SWB. While, Natvig et al (2003) found no significant differences between boys and girls with respect to their reported level of subjective well-being. However, the Present finding is in contradiction with the finding of Haller and Hadler (2006) who found that women scored significantly higher both on happiness and life satisfaction in every field of life.…”
Section: Discussionmentioning
confidence: 57%
“…Although there are limited studies that focus on primary students, Suldo, Riley and Shaffer (2006) point out in their review of academic correlates and life satisfaction for adolescents, that IQ, grade point averages and diagnosed learning disabilities were not strong indicators of life satisfaction, while care and support was a factor. Further, Natvig, Albrektsen and Qvarnstrom (2003) in their exploration of whether academic competence was associated with adolescent happiness, found no such evidence, rather their research pointed to social skills (as in the ability to cope with bullying, making friends and getting involved in school activities) as being strongly connected. Finally, Van Petegem, Aelterman, Rosseel and Creemers (2007) identified that student wellbeing is directly affected by interpersonal relationships that exist with teachers.…”
Section: Student Intellectual Status and Happinessmentioning
confidence: 92%
“…The terms well-being and happiness have been used interchangeably (Natvig et al, 2003;Veenhoven, 1991), yet happiness and satisfaction are two distinct spheres of well-being (Peíro, 2006). Studies examining adolescent perceptions of life satisfaction have connected it to five distinct domains: family, friends, school, self and the living environment (Natvig et al, 2003;Cicognani et al, 2008;Konu et al, 2002). Gender differences in self-rated well-being are found to be less obvious than with self-rated health (Currie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%